2017
DOI: 10.1007/8904_2017_80
|View full text |Cite
|
Sign up to set email alerts
|

Expert Opinion vs Patient Perspective in Treatment of Rare Disorders: Tooth Removal in Lesch-Nyhan Disease as an Example

Abstract: Treatment recommendations for rare disorders often are limited by a lack of data from objective clinical trials. As a result, recommendations are often based on expert opinion. Because expert opinions sometimes conflict, many patients turn to the Internet for guidance from others who may have tried a treatment. The increasing numbers of patients and families who post opinions regarding outcomes allow for systematic data collection regarding specific treatments from the patient perspective. We used social media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, there is no high-quality evidence to support any drug treatment for SIBs. In nondrug therapy, pediatricians and patients’ caregivers also supported tooth extraction as one of the important means to control SIB ( James et al, 1989 ; Cotton et al, 2018 ), while dental experts preferred to rely on tooth protectors or lip protectors to reduce injuries ( Limeres et al, 2013 ). Jinnah et al suggested that rapid tooth extraction should be considered as part of the nursing standard when necessary ( Goodman et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no high-quality evidence to support any drug treatment for SIBs. In nondrug therapy, pediatricians and patients’ caregivers also supported tooth extraction as one of the important means to control SIB ( James et al, 1989 ; Cotton et al, 2018 ), while dental experts preferred to rely on tooth protectors or lip protectors to reduce injuries ( Limeres et al, 2013 ). Jinnah et al suggested that rapid tooth extraction should be considered as part of the nursing standard when necessary ( Goodman et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Internet again offers promising opportunities for lay people, including people living with RDs and their families, to find information, learn about and participate in research. In this context, social media networks and online patient communities have been consolidating their role as research engagement, recruitment, health information-sharing and discussion forums [8,[28][29][30][31][32]. This study's rationale relies on a double-sided hypothesis: (i) that a people-centric, multi-stakeholder, multilingual, web-based intervention in CDG-combining research empowerment and engagement strategiesimproves recruitment and participation, and; (ii) that this innovative methodology based on an e-questionnaire is an effective clinical data collection approach, namely in the field of immunology [10].…”
Section: Introductionmentioning
confidence: 99%